Sling blade [videorecording (DVD)] - Thornton, Billy Bob; Yoakam, Dwight; Walsh, J. T.; Ritter, John, 1948-2003; Black, Lucas, 1982-; Canerday, Natalie; Duvall, Robert (Miramax Films : Distributed by Buena Vista Home Entertainment, 2011)
After 25 years, mildly retarded killer Karl Childers is released from the mental hospital where he was placed for killing his mother and her lover. He gets a job and is befriended by a fatherless boy and his mother, but his newfound peace is shattered by the mother's abusive boyfriend.